THE RELEVANCE OF CONTEMPORARY ANALYSIS PHILOSOPHY IN ISLAMIC STUDIES (STUDYING THE PHILOSOPHY OF CHARLES SANDERS PIERCE'S PRAGMATISM IN THE CONTEMPORARY ANALYTIC PHILOSOPHY) - Rezki Putri Nur Aini (Dirosatuna: Journal of Islamic Studies, 2021)
The transformation of philosophical studies which necessitates a shift in the scope of discussion from fundamental themes around the nature and general doctrine which tends to stagnate to become more diverse and adapt to the times, provides a glimmer of hope for the future of Islamic studies which has been confined to the stability of fundamental problems. These dynamics offer the opportunity for the entry of various schools of new philosophy and thought that are more relevant to explain the current situation. One of them is the philosophy of pragmatism that was introduced by Charles Sanders Peirce through his claim regarding the primacy of understanding and benefits in proving the truth. A truth will only be accepted if it has been through investigations and trials or experimental proofs in terms of its practicality and usefulness until the truth really messages and gives meaningful meaning. In Islamic studies, the method used by Peirce then becomes very important in resolving internal Islamic conflicts caused by fanaticism between groups because of their existence towards truth claims.